Wellness Program Within Primary Health Care: How to Avoid "No Show" to Planned Appointments? – A Patient-Centred Care Perspective. Issue 1 (16th April 2021) - Musa, Sarah; Al Baker, Wadha; Al Muraikhi, Hissa; Nazareno, Deborah; Al Naama, Abdullah; Dergaa, Ismail
Background: Wellness program is a service provided by Primary Health Care Corporation (PHCC) to deliver an exercise program dedicated to patients with unhealthy lifestyle. Failing to cancel health care appointments in advance "no show" results in a vacant appointment slot that cannot be offered to other patients, which in turn will have an adverse impact on management plan and expected health outcome measures. Objectives: The purpose of this study is to implement a patient-centred care (PCC) program as an interventional approach to engage patients in changing behaviour and to encourage self-awareness to improve health status. Another aim of this study is to evaluate the effectiveness of an appointment reminder system (either short message service (SMS) or telephone call) on completion rate of the 12-week Wellness program. Methods: Amongst 112 patients, 50 participants (age: 49.9 ± 12.56 years; height: 1.61 ± 0.08 m; body mass: 75.06 ± 15 kg; body mass index (BMI): 28.66 ± 3.51 kg/m 2 ) completed two surveys as part of the PCC program. The first survey was regarding the appointment reminder's method preference. Accordingly, the demanded reminder system has been implemented as per patients' preferences and then the rate of completion of the 12-weeks-wellness-program has been compared to the months preceding the intervention to demonstrate the effectiveness of this new reminder system. Towards the end of the study, a second survey on patients' satisfaction level with regard the new reminder system has been completed. Results: The PCC program showed that majority of the patients were in favour of an appointment reminder system through SMS text message and telephone calls. Implementing this tool based on patient preference resulted in a high improvement of the completion rate of the Wellness program. Conclusions: This study provides insight on the efficacy of implementing a PCC program in Wellness Centre as well as the effectiveness of an appointment reminder system in improving the completion rate of Wellness program in a primary health care facility. Completing the Wellness program may lead to improved lifestyle behaviour and health outcomes by complying with international physical activity recommendations from the American College of Exercise Medicine (ACEM) and the World Health Organization (WHO).